2021
DOI: 10.1029/2021gl094137
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Responses of Idealised and Realistic Simulations of Shallow Cumuli to Aerosol Perturbations

Abstract: Shallow clouds remain greatly significant in improving our understanding of the atmosphere. Using the Met Office Unified Model, we compare highly idealised simulations of shallow cumuli with those using more realistic domains, with open lateral boundaries and varying large‐scale forcing. We find that the realistic simulations are more capable of representing the cloud field on large spatial scales, and appear to limit the aerosol perturbations leading to impacts on the thermodynamic conditions. Aerosol perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, traditionally, these tools are unable to directly account for changes in the dynamics and thermodynamics of the large‐scale climate system, and hence lack an important component of clouds' response (Abbott & Cronin, 2021; Anber et al., 2019). For example, it was recently shown that the representation of large‐scale effects on the CRM domain, that is, the lateral boundary conditions or “large‐scale forcing” (LSF), could artificially determine clouds' response to aerosol perturbation (Dagan, Stier, Spill, et al., 2022; Spill et al., 2021). Specifically, it was shown that the recent efforts to couple local cloud response with changes in the large‐scale vertical velocity (Abbott & Cronin, 2021) could result in an unrealistic increase in the environmental humidity and thus overestimate clouds' sensitivity to aerosols (Dagan, Stier, Spill, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, traditionally, these tools are unable to directly account for changes in the dynamics and thermodynamics of the large‐scale climate system, and hence lack an important component of clouds' response (Abbott & Cronin, 2021; Anber et al., 2019). For example, it was recently shown that the representation of large‐scale effects on the CRM domain, that is, the lateral boundary conditions or “large‐scale forcing” (LSF), could artificially determine clouds' response to aerosol perturbation (Dagan, Stier, Spill, et al., 2022; Spill et al., 2021). Specifically, it was shown that the recent efforts to couple local cloud response with changes in the large‐scale vertical velocity (Abbott & Cronin, 2021) could result in an unrealistic increase in the environmental humidity and thus overestimate clouds' sensitivity to aerosols (Dagan, Stier, Spill, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%